The Role of Cornelis Chastelein in the Development of the Depok Region, 1693-1714 - Hari Naredi; Ahmad Ruslan; Amar Septian; Nunung Siti Nurjanah; Anwar Jadid; Fras Bagaskara; Iqbal Gagah Soekarno; Imam Rizki Al Fatih (IHiS (Indonesian Historical Studies), 2021)
In the course of its history, The Depok area has had interesting dynamics. The growth of Depok has been inseparable from the people who originally settled in the area. Depok’s emergence and growth as a city has been due to in large part the role of Cornelis Chastelein. At the end of the 17th century, he plotted the area of Depok and since then, it began to witness growth and development of that area. This study analyzes the traces and relics of Cornelis Chastelein in Depok in the period 1693 and 1714. It uses historical analysis technique in which carried out through four stages, consist of heuristics, verification, interpretation, and historiography. According to the study, it shows that the history of Depok cannot be separated from Chastelein. His legacy in the form of colonial buildings can be found in the Depok area, West Java. Apart from the visible physical legacy, Chastelein also freed slaves, allowing them to live independently and become the original residents of Depok.